If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 9 + 3x = -11 Reorder the terms: 9 + 7x + 3x = -11 Combine like terms: 7x + 3x = 10x 9 + 10x = -11 Solving 9 + 10x = -11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 10x = -11 + -9 Combine like terms: 9 + -9 = 0 0 + 10x = -11 + -9 10x = -11 + -9 Combine like terms: -11 + -9 = -20 10x = -20 Divide each side by '10'. x = -2 Simplifying x = -2
| 28-a+4a= | | 9+3x+5x=-55 | | X^2-9x+84=0 | | 7+(1.2b-3)+(-1.4b+2)=-12b+38 | | 28r^3=63r | | k^2+2=0 | | -7n-4-9n=-20 | | 5-2x-2x=-31 | | 8x^6-16x^4= | | 3(-x+4)= | | -34=3(4s+9) | | x^2+1+8sin(2x)=0 | | X-0.2x=20000 | | 7r-9=23 | | 3a^2+10=253 | | 1-y/3=2/5 | | -4-3b+2+5b= | | 2.7p=-10.8 | | 3-6*2+2= | | 7x^2-1=636 | | m/3+9=2 | | 3(n+2)-16=8n | | X-2=54 | | 3secx=-6 | | 5x+10-5=35 | | [2w-7]+3=14 | | 3x+2=2a+5 | | 1200=900+300z | | -12=2+5 | | 4x+10=6x+10 | | 2a-8b=12 | | 6-10r^2=-274 |